Paneth and Intestinal Stem Cells are Differentially Affected during Worsening of Acute Cellular Rejection in Small Bowel Transplantation compared to Intestinal Ischemia Reperfusion Injury and Graft versus Host Disease. (July 2018) - Molinaris, Melisa Pucci; Polo, Virginia Gonzalez; Ramisch, Diego; Meier, Dominik; Rumbo, Martin; Gondolesi, Gabriel E
Abstract : Instituto de Estudios Inmunológicos y Fisiopatológicos, UNLP-CONICET, La Plata, Argentina. Introduction: Acute cellular rejection (ACR) is one of the leading causes of graft loss after small bowel transplantation (SBTx). Although crypt epithelial cell apoptosis is used as histopathological criteria for ACR diagnosis, it is not clear which of epithelial lineages are the target of ACR. It was shown that the number of enteroendocrine progenitor cells in intestinal crypts was reduced during mild ACR, however, no results on other cell types of the crypt have been depicted so far. The aim of our work was to elucidate integrity and functionality of Paneth and stem cells during different degrees of ACR, in comparison with other clinical conditions such as graft vs. host disease (GVHD) and ischemia reperfusion injury (IRI). Material and Methods: 44 patients of SBTx and controls treated in our center between 2006 and 2016 were included in the study. Rejection diagnosis was established by an experienced pathologist according to the recommendations of the pathology workshop of the VIII Small Bowel Transplantation Symposium. We compared small biopsies from SBTx patients with no, mild, moderate or severe ACR by immunohistochemistry and quantitative PCR (n=10 per group as average) for different cell markers (Lgr5, lysozyme, defensin5, IL22R, Ki67). Other conditions such as different degree of intestinal GVHD and IRI were included as separate groups. Comparisons among groups of data were performed with the Kruskal-Wallis test and the Dunn`s post-test when more than two groups were analyzed, whereas the Mann-Whitney U test was chosen to compare data from two groups. Results and Discussion: Using differential immunofluorescence counting of different markers we observed that numbers of Paneth and stem cells remain constant in all ACR groups, whereas the transit-amplifying zone is the region that concentrates most of the apoptotic bodies during ACR (p<0.05). We detected unchanged level of antimicrobial peptides in Paneth cells and similar numbers of Ki-67+IL-22R+ stem cells revealing cell functionality in moderate ACR samples. Oppositely, in GVHD of moderate to severe, as well as IRI, Paneth cell number and markers were diminished (p<0.05), indicating differential mechanism that operate to trigger epithelial cell apoptosis in different situations. Conclusion: Paneth and stem cells are not primary target cells during ACR. IL-22R + Ki-67+ stem cells might be an interesting target cell population for protection and regeneration of the epithelial monolayer during/after a severe ACR in ITx patients.